Felicitas (eudaimonia) ou les promenades d'Érasme dans le jardin d'Épicure - Bietenholz, Peter (Renaissance and Reformation / Renaissance et Réforme, 2006)
An examination of Erasmus' changing views of Epicureanism must primarily rely on statements by himself that refer to Epicurus or indicate awareness of, and perhaps affinity with, some aspects of his philosophy. A brief first part will survey the intermediate sources for Epicurus' system, classical and patristic, appreciative or critical, with which Erasmus was familiar. Thereafter the procedure will be chronological, examining first the early traces of Erasmus' acquaintance with Epicurus, leading to an attempt to reconcile his moral philosophy with the Gospel teachings. Next Erasmus' years in Italy are considered. Italy had recently experienced a marked revival of interest in Epicurean thought, leading to a positive revaluation. Here Erasmus' familiarity with the work of Lorenzo Valla obtains a crucial importance. Valla turned Erasmus, to put it boldly, into a sort of convert to Epicureanism, as will be shown by a fresh look at his Moriae encomium. After the Moria Erasmus' statements relevant to Epicureanism tend to be more casual and inconsistent. In the end, however, we notice a reawakening of concern and almost a return to his initial endorsement of a Christian Epicureanism. The history of Epicureanism is an ongoing, often radical, quest for enduring felicity, although not always proceeding from the same intellectual premises. Finally, a brief attempt is made to assign Erasmus his modest place in that history.